2017
DOI: 10.3389/fmolb.2017.00058
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pontin and Reptin in Cellular Physiology and Cancer Etiology

Abstract: Pontin (RUVBL1, TIP49, TIP49a, Rvb1) and Reptin (RUVBL2, TIP48, TIP49b, Rvb2) are highly conserved ATPases of the AAA+ (ATPases Associated with various cellular Activities) superfamily and are involved in various cellular processes that are important for oncogenesis. First identified as being upregulated in hepatocellular carcinoma and colorectal cancer, their overexpression has since been shown in multiple cancer types such as breast, lung, gastric, esophageal, pancreatic, kidney, bladder as well as lymphatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 203 publications
(437 reference statements)
8
101
0
Order By: Relevance
“…Both high LOXL2 levels and its perinuclear localization are associated with poor outcome and lower survival rates of patients with breast cancer (Ahn et al, 2013;Moreno-Bueno et al, 2011). Furthermore, both RUVBL2 and CRL4B complex are also known to play important roles in cancer biology (Grigoletto et al, 2011;Grigoletto et al, 2013;Jang et al, 2018;Mao and Houry, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both high LOXL2 levels and its perinuclear localization are associated with poor outcome and lower survival rates of patients with breast cancer (Ahn et al, 2013;Moreno-Bueno et al, 2011). Furthermore, both RUVBL2 and CRL4B complex are also known to play important roles in cancer biology (Grigoletto et al, 2011;Grigoletto et al, 2013;Jang et al, 2018;Mao and Houry, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that G9a-dependent methylation of the nonhistone substrate RUVBL2 (REPTIN, TIP48, TIP49b) can repress HIF1a-mediated transcription (Lee et al, 2010). RUVBL2 has also been shown to antagonize b-catenin activity (Bauer et al, 2000;Mao and Houry, 2017). We reasoned that the non-histone substrate, RUVBL2, might function to repress b-catenin activity through a G9a-mediated mechanism.…”
Section: G9a Restrains Tcf4 Gene Transcription By Repressing Chromatimentioning
confidence: 94%
“…Pont do not have any RNA binding domains (Mao and Houry, 2017). Therefore, it is likely 407 that additional proteins, not Rept and Pont themselves, physically interact with constituent 408 mRNAs for kl-granule formation.…”
Section: Axoneme 321mentioning
confidence: 99%
“…Function of Reptin and Pontin in dynein assembly 376A wide range of functions have been assigned to Rept-and Pont-containing complexes 377 including roles in chromatin remodeling, transcription regulation, DNA repair and ribosome 378 assembly(Mao and Houry, 2017). They can act alone, together or as part of larger complexes 379(Huen et al, 2010; Kakihara and Saeki, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation